2021
DOI: 10.1016/j.tranon.2021.101103
|View full text |Cite
|
Sign up to set email alerts
|

An upward 9.4 T static magnetic field inhibits DNA synthesis and increases ROS-P53 to suppress lung cancer growth

Abstract: Highlights Upward 9.4 T SMF exposure for 88 h significantly inhibited A549 tumor growth in mice. 9.4 T SMF treatment for 88 h had no severe impairment to the mice key organs or blood cell count. Upward 9.4 T SMF treatment for 24 h caused A549 DNA synthesis inhibition. Upward 9.4 T SMF treatment for 24 h significantly increased ROS and P53 levels, and caused G2 cell cycle arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Moreover, Csillag et al placed human lung cancer cells (A549) in 389 mT SMF for 30 minutes and observed an obvious decrease in ROS levels [ 34 ]. On the contrary, our previous study showed that 9.4 T SMF could significantly increase A549 cellular ROS levels [ 20 ]. It is obvious that SMFs with different parameters could generate various effects on cancer cells.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Moreover, Csillag et al placed human lung cancer cells (A549) in 389 mT SMF for 30 minutes and observed an obvious decrease in ROS levels [ 34 ]. On the contrary, our previous study showed that 9.4 T SMF could significantly increase A549 cellular ROS levels [ 20 ]. It is obvious that SMFs with different parameters could generate various effects on cancer cells.…”
Section: Discussionmentioning
confidence: 80%
“…To further examine the effects of moderate SMFs on ovarian cancer cells, we used a superconducting magnet that has a cell culture compatible system ( Figure 4(a) ) [ 20 ]. We placed the cells at the upper part of the magnet where the intensity of SMF is ~0.5 T. Similar to the permanent magnet, this 0.5 T SMF also significantly decreased HO8910 and SKOV3 ovarian cancer cell invasion ( Figure 4(b) ) and migration ( Figure 4(c) ) in Transwell assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study 24 showed a different impact of opposite polarity magnetic elds on hematological parameters of spontaneously hypertensive rats. Another recent study 25 found that long-term exposure (88 h) of a MF of 9.4 T (Tesla) strength (planned for use in magnetic resonance imaging) signi cantly inhibited tumor growth (up to 41%) in mice with lung cancer. This effect was observed only with exposure to the magnetic north pole.…”
Section: Introductionmentioning
confidence: 99%